The Fixed Points of Solutions of Some q-Difference Equations - Xiu-Min Zheng; Hong-Yan Xu; Jun-Feng Xu (Abstract and Applied Analysis)
The purpose of this paper is to investigate the fixed points of solutions f(z) of some q-difference equations and obtain some results about the exponents of convergence of fixed points of f(z) and f(qjz)  (j∈N+), q-differences Δqf(z)=f(qz)-f(z), and q-divided differences Δqf(z)/f(z).